2019
DOI: 10.1016/j.celrep.2019.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Color Categorization Independent of Color Naming

Abstract: Highlights d Are color categories an example of linguistic impact on nonverbal human cognition? d Patient RDS shows impairment in naming colors after a lefthemisphere stroke d The lesion disconnects color-biased visual regions from the language system d Relative sparing of color categorization shows its independence from color naming

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
35
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 75 publications
(105 reference statements)
5
35
2
Order By: Relevance
“…These left middle temporal clusters overlapped with the regions that were functionally disconnected from colorsensitive visual cortex in a patient with color anomia (see Fig. 3C and Siuda-Krzywicka, Witzel, et al, 2019). Accordingly, participants who were faster at naming colors had stronger functional connectivity between the left posterior seed and the anterior temporal clusters disconnected in this patient ( Analyses using an anatomically-defined Regions of Interest (ROI) confirmed the above voxelwise results ( Fig.…”
Section: Color Naming and Functional Connectivity Of The Left-hemisphsupporting
confidence: 71%
See 3 more Smart Citations
“…These left middle temporal clusters overlapped with the regions that were functionally disconnected from colorsensitive visual cortex in a patient with color anomia (see Fig. 3C and Siuda-Krzywicka, Witzel, et al, 2019). Accordingly, participants who were faster at naming colors had stronger functional connectivity between the left posterior seed and the anterior temporal clusters disconnected in this patient ( Analyses using an anatomically-defined Regions of Interest (ROI) confirmed the above voxelwise results ( Fig.…”
Section: Color Naming and Functional Connectivity Of The Left-hemisphsupporting
confidence: 71%
“…These converging results indicate that the communication between the left posterior color region and the left middle temporal gyrus is causally related to color naming abilities. We suggested that the left sided color-sensitive regions may act as a cortical naming hub linking color perception with color names (Siuda-Krzywicka and Bartolomeo, 2019; Siuda-Krzywicka, Witzel, et al, 2019). The current results allow us to narrow down this hypothesis to the posterior color region, which would serve as the color naming hub, and whose lesions would lead to color anomia.…”
Section: A Color Naming Hub ?mentioning
confidence: 61%
See 2 more Smart Citations
“…We showed that RDS could categorize colors independently from his ability to name them. Color categorization may thus constitute a separate module of color processing rather than result from the interaction between color perception and language (Siuda-Krzywicka and others 2019b).…”
Section: Modules Of Cortical Color Processingmentioning
confidence: 99%